Antioxidant, antidiabetic and antibacterial activities of curd derived from selected plants fortified with ocimum tenuiflorum - Jaya Vejayan, Palliah; Sharifah Aminah, Tuan Said; Ahmad, M. Farid; Hani K., Agustar; Srikumar, Chakravarthi (Faculty of Pharmacy, University of Benin, 2022)
Mangifera indica cv. Apple (mango), Ananas comosus cv. Sarawak (pineapple) and Morinda citrifolia (noni) are associated with the milk-clotting ability. While Ocimum tenuiflorum (holy basil) known to have phytochemicals with important biological activities. In this study, the aim was to determine the extent of O. tenuiflorum in providing biological activities to the curd achieved by the three milk-clotting plants. A freeze-dried mixture of plant extracts in the ratio of 1:1:1 was prepared from the kernel of M. indica and fruits of A. comosus and M. citrifolia to form a natural milk-clotting agent. The curd was fortified with O. tenuiflorum, which was then examined for antioxidant activities utilising the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and Ferric Reducing Antioxidant Power (FRAP) assay. The anti- diabetic action was determined using an α-amylase inhibiting test, whereas the antibacterial activity was determined using the agar well diffusion method on selected bacteria. The results for DPPH, FRAP and alpha-amylase inhibitory assays for the fortified curd with O. tenuiflorum showed IC50 values of 1.47±3.82 mg/mL, 370.8±0.3 mg GAE/g and 3.19±1.59 mg/mL, respectively. Antibacterial activity was found in the O. tenuiflorum fortified curd against two Gram-positive bacteria (S. aureus and B. cereus) and three Gram negative bacteria (S. marcescens, E. coli and A. baumannii), all with MIC of 2.3 mg/mL. In conclusion, the O. tenuiflorum evaluated to enhance the anti-oxidative, anti-diabetic and antimicrobial properties of the curd achieved by the combined effects of M. indica, A. comosus and M. citrifolia.